Analysis of Transformational Leadership and Work Stress on Employee Performance with Job Satisfaction as A Mediating Variable at The Tax Service Office Pratama Medan Belawan - Affandy, Ahmad; Rahayu, Sri; Erwansyah, Erwansyah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is a key factor in supporting the success of public organizations, including the Medan Belawan Tax Office (KPP), which has strategic responsibilities in state revenue and taxpayer services. High target demands, workloads, and the dynamics of taxation policies require employees to perform optimally. This study aims to analyze the influence of transformational leadership and work stress on employee performance with job satisfaction as a mediating variable at the Medan Belawan Tax Office. This study uses a quantitative approach with a census method of 100 permanent employees. Primary data were collected through questionnaires and analyzed using Partial Least Square (PLS) with the help of SmartPLS. The results show that transformational leadership has a positive but insignificant effect on employee performance, but has a positive and significant effect on job satisfaction. Work stress has a negative and significant effect on employee performance and job satisfaction. Job satisfaction has a positive and significant effect on employee performance. In addition, job satisfaction mediates the effect of transformational leadership and work stress on employee performance. These findings indicate that improving employee performance in the KPP Pratama Medan Belawan environment is more effectively done through strengthening job satisfaction, managing work stress, and implementing consistent transformational leadership. This study is expected to contribute theoretically to the development of human resource management in the public sector and provide practical recommendations for tax agency leaders.